Internet use and life satisfaction among empty nesters in rural areas of Yangzhou: based on propensity score matching and mediating effect model - Yitong Liu; Yaning Wang; Zhuoya Yang; Wenkun Xu; Guangyu Tian; Yuexiao Gao; Miaomiao Zhao; Rujian Lu; Yaqin Zhong (BMC Geriatrics)
Abstract Background Empty nesters represent a unique group that deserves focused attention. Internet usage is becoming increasingly prevalent among older people. This study preliminarily discussed the differences in life satisfaction between empty nesters who used the Internet and those who did not. This study also provided insight into how Internet use interacted with social participation to improve their life satisfaction. Methods A face-to-face survey was conducted in Yangzhou City, China, from July to August 2022. Covariates related to life satisfaction, such as sociodemographic characteristics and participants’ health behaviors, were collected. Propensity Score Matching (PSM) was used to match Internet users with non-Internet users. Binomial logistic regression was employed to analyze the association between Internet use and life satisfaction, and the KHB method was used to examine the mediating effect. Results 1,177 respondents aged 60 and above were ultimately matched for analysis in this study. The results showed that Internet use was significantly correlated with higher levels of both social participation (β = 0.276, P < 0.05) and life satisfaction (β = 0.433, P < 0.05). Social participation partially mediated the relationship between Internet use and life satisfaction, with a mediating effect of 0.112 accounting for 21% of the total effect. Further analysis of group heterogeneity indicated that the positive association between Internet use and life satisfaction was more prominent among participants who were younger, male, unemployed, had an income, and were in relatively healthy conditions. Conclusions Internet use was crucial in promoting social participation and enhancing life satisfaction among rural empty nesters. Interventions aimed at improving their life satisfaction should prioritize the creation of inclusive and supportive environments, encouraging social participation, and enhancing digital literacy.